A qualitative approach to assessing work ability. - Tengland, Per-Anders (Work, 2013)
PROBLEM: We often need to be able to assess the extent to which individuals have or lack work ability. For this we need instruments. Most of the instruments available have flaws. They either lack validity or they use roundabout methods when collecting information about the individual's work ability. OBJECTIVES: The aim of this paper is to present a conceptual model for constructing a questionnaire that can be used for assessing work ability. METHODS: The methods used are philosophical, i.e. analytical and deductive. A conceptual theory is provided, and based on the resulting definition of the concept of "work ability" conclusions are drawn regarding how to assess work ability. RESULTS: When constructing quantitative instruments, we can increase validity through using a more strict definition of work ability. However, such an approach will only solve some of the problems noted above. The proposal is, instead, to create a qualitative questionnaire, founded on a definition of "work ability", which focuses on the concrete problems concerning the work ability of the individual. Finally, a sketch of such an instrument is provided, with questions covering all the relevant aspects of work ability. CONCLUSION: The qualitative questionnaire proposed is believed to be superior to more traditional (quantitative) instruments for assessing a person's work ability, as well as for finding solutions to her problems concerning work ability.